The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.2527/tas2016.0009
|View full text |Cite
|
Sign up to set email alerts
|

A summary review of carcass cutability data comparing primal value of immunologically and physically castrated barrows

Abstract: The objectives were to 1) assess cutability, quality, and value of carcasses from immunologically castrated (IC) barrows compared with carcasses from physically castrated (PC) barrows and 2) evaluate the effect of hot carcass weight (HCW) on cutability and value of IC barrows summarizing U.S. data. Lean cutting yield (LCY) was defined as: LCY = [(whole ham + trimmed loin + Boston butt + picnic + spareribs)/chilled side wt] x 100. Carcass cutting yield (CCY) was determined using the following equation: CCY = [(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…But recent investigations indicated lower WHC of EM than SC meat assessed either as drip loss ( Batorek et al, 2012b ; Aluwé et al, 2013 ; Škrlep et al, 2019 ) or cooking loss ( Channon et al, 2016 ; Van den Broeke et al, 2016 ; Škrlep et al 2019 ). Lower WHC assessed as drip loss was also reported for IC compared to both EM ( Batorek et al, 2012a ) and SC ( Lowe et al, 2014 ; Harsh et al, 2017 ; Seiquer et al, 2019 ). In accordance with the present investigation, several studies demonstrated higher cooking loss in IC than SC ( Boler et al, 2012 ) while being similar to EM ( Batorek et al, 2012b ; Van den Broeke et al, 2016 ), whereas some data ( Aluwé et al, 2013 ; Akit et al, 2014 ) show even higher cooking loss of IC than EM.…”
Section: Discussionmentioning
confidence: 80%
“…But recent investigations indicated lower WHC of EM than SC meat assessed either as drip loss ( Batorek et al, 2012b ; Aluwé et al, 2013 ; Škrlep et al, 2019 ) or cooking loss ( Channon et al, 2016 ; Van den Broeke et al, 2016 ; Škrlep et al 2019 ). Lower WHC assessed as drip loss was also reported for IC compared to both EM ( Batorek et al, 2012a ) and SC ( Lowe et al, 2014 ; Harsh et al, 2017 ; Seiquer et al, 2019 ). In accordance with the present investigation, several studies demonstrated higher cooking loss in IC than SC ( Boler et al, 2012 ) while being similar to EM ( Batorek et al, 2012b ; Van den Broeke et al, 2016 ), whereas some data ( Aluwé et al, 2013 ; Akit et al, 2014 ) show even higher cooking loss of IC than EM.…”
Section: Discussionmentioning
confidence: 80%
“…Primal and retail cut weights were multiplied by the associated price, then converted to value per kg. Best-, worst-, and 4-year (2013–2017) average pricing scenarios were calculated similar to the manner described by Harsh et al (2017) . The best (2014) scenario was determined when average pork carcass prices were the most elevated.…”
Section: Methodsmentioning
confidence: 99%
“…Improvest (marketed under the trade name of Improvac, Innosure, or Vivax in some parts of the world; Zoetis Inc., Parsippany, NJ, USA) is a gonadotropin-releasing factor (GnRF) analog-diphtheria toxoid conjugate formulated product approved for the temporary suppression of testicular function and reduction of boar taint in intact male pigs intended for slaughter. Managing male pigs with Improvest has several secondary production advantages when compared with physically castrated (PC) male pigs, including 1 to 2 percentage unit improvement in preweaning livability, the management of ridgling pigs, 4% to 6% less feed consumption during the grow-finish period, 4% to 8% improvement in weight gain during the grow-finish period, 8% to 12% improvement in feed efficiency during the grow-finish period, and 1.0% to 1.5% unit improvement in cutting yields of merchandized meat cuts ( Čandek-Potokar et al, 2017 ; Harsh et al, 2017 ; Needham et al, 2017 ; Poulsen Nautrup et al, 2018 ). Nutritional recommendations for male pigs managed with Improvest differ from those of PC males, which is attributed to differences in feed consumption and lean growth ( Dunshea et al, 2013 ; Rueff et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%